The impact of integrative neuromuscular training on the physical fitness of elite male martial arts Sanda Athletes - Zhenxing Li; Jia Sun; Rozaireen Muszali; Liang Li (PLoS ONE, 2026)
Objective Integrative Neuromuscular Training (INT) is recognized not only for its potential in preventing sports injuries but also for enhancing athletic performance. Understanding the relationship between INT and the physical qualities of elite Sanda athletes is important for addressing performance limitations in elite Sanda athletes. While INT has been applied in various sports, there is a lack of research in the context of Sanda. This empirical study aims to investigate the effects of INT on the physical qualities of elite Sanda athletes. Methods A randomized controlled trial design was employed, with 26 elite male Sanda athletes randomly assigned to either the Integrative Neuromuscular Training group (INT, n = 13) or the control group (CON, n = 13). The INT group engaged in three sessions of INT training per week, lasting 45 minutes each for 12 weeks, while the CON group completed a conventional conditioning program. Pre- and post-intervention assessments included one-repetition maximum tests (1RM), 30-meter sprint tests (30MST), counter movement jump tests (CMJ), reaction agility tests (RAT), and Y balance tests (YBT). Results Post-intervention, the INT group showed significant improvements in these physical fitness measures: [1RM bench press (p < 0.001, d = 2.599), 1RM squat (p < 0.001, d = 2.610), T-5m (p = 0.011, d = −1.000), T-10m (p = 0.011, d = −0.833), T-30m (p < 0.001, d = −6.120), CMJ (p < 0.001, d = 4.236), RAT (p < 0.001, d = −3.312), YBT-L (p < 0.001, d = 3.075), YBT-R (p < 0.001, d = 2.722)]. In the CON group, there were no significant changes in physical quality test scores post-intervention. Relative changes from pre- to post-intervention indicated no significant differences in △-T-5m between INT and CON groups, while significant differences were found in other physical quality assessments [△-1RM bench press (3.376 vs 0.220 kg, p < 0.001), △-1RM squat (3.665 vs −0.533 kg, p < 0.001), △-T-10m (−0.005 vs 0.005 s, p = 0.004), △-T-30m (−0.153 vs −0.017 s, p < 0.001), △-CMJ (4.846 vs 0.615 cm, p < 0.001), △-RAT (−0.048 vs −0.002 s, p < 0.001), △-YBT-L (5.154 vs −0.615, p < 0.001), △-YBT-R (5.615 vs −0.308, p < 0.001)]. Conclusion A 12-week INT intervention significantly enhances the physical qualities of Sanda athletes. The overall improvements in the INT group across 1RM, 30MST, CMJ, RAT, and YBT tests demonstrate that the INT program may serve as an effective conditioning strategy for improving selected physical fitness outcomes in elite Sanda athletes.